2021
DOI: 10.3390/separations8120244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasound-Assisted Pretreatment on Extraction Efficiency of Essential Oil and Bioactive Compounds from Citrus Waste By-Products

Abstract: Waste or by-product use is in focus for reducing the environmental threat and acquiring wealth out of waste. The current study aim was to investigate the effects of ultrasound pretreatment on the extraction of bioactive compounds and composition of essential oils extracted from citrus waste. The response surface methodology (RSM) was used to optimize higher yield extraction parameters. Pretreatment of ultrasound-assisted extraction recovered 33% enhanced yield with reduced time and was economical as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Therefore, obtaining yield in large quantities requires several parameters, such as extraction methods, amount of biomass, environmental conditions (pH, temperature, humidity), and extraction time (Liu et al 2022;Monagas et al 2022;Nortjie et al 2022). The selection of pre-treatment and processing methods affects the reduction time for extraction, an increase in yield, the quality of biological compounds, and energy reduction (Zhang et al 2018;Sandhu et al 2021;Patra et al 2022). For example, drying impacts the metabolites of heat-sensitive components, and the process can also contribute to improving the conservation of bioactive compounds against oxidation, enzymatic activity, and putrefactive bacteria and allows cell destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, obtaining yield in large quantities requires several parameters, such as extraction methods, amount of biomass, environmental conditions (pH, temperature, humidity), and extraction time (Liu et al 2022;Monagas et al 2022;Nortjie et al 2022). The selection of pre-treatment and processing methods affects the reduction time for extraction, an increase in yield, the quality of biological compounds, and energy reduction (Zhang et al 2018;Sandhu et al 2021;Patra et al 2022). For example, drying impacts the metabolites of heat-sensitive components, and the process can also contribute to improving the conservation of bioactive compounds against oxidation, enzymatic activity, and putrefactive bacteria and allows cell destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The improved extraction method not only benefits these industries but also promotes sustainability by reducing resource and energy consumption, making it an environmentally friendly and cost‐effective approach. As a result, ultrasound‐assisted extraction is poised to enhance the overall value and versatility of EOs for industrial use (Sandhu et al., 2021).…”
Section: Extraction Techniques For Essential Oilsmentioning
confidence: 99%
“…The utilization of ultrasound energy or ultrasonic to assist the valorization or extraction of the agro-industrial biomass based on lignocellulosic materials to produce value-added products has been widely reported. Ultrasound pretreatment is a useful alternative process based on the reduction of an adverse effect on the extractable compound, limiting the use of organic solvent consumption, lowering the temperature, and a reduction in the extraction time [61] . Other than that, the hybrid system of combining ultrasound with other pretreatment processes is an alternative to increase the efficiency of the pretreatment process.…”
Section: Role Of Ultrasound Technology In the Conversion Of Agricultu...mentioning
confidence: 99%
“…Other than that, an ultrasound-assisted extraction process is also adopted for the extraction of bioactive compounds. Sandhu et al, [61] used ultrasound pretreatment to see its effect on the extraction of bioactive compounds and the composition of essential oils extracted from citrus waste. This study found that ultrasound pretreatment led to 33% enhanced yield with reduced time and was much economically viable compared to the conventional hydro-distilled process.…”
Section: Role Of Ultrasound Technology In the Conversion Of Agricultu...mentioning
confidence: 99%